2020
DOI: 10.1016/j.jpowsour.2020.228579
|View full text |Cite
|
Sign up to set email alerts
|

Enabling high areal capacity for Co-free high voltage spinel materials in next-generation Li-ion batteries

Abstract: The rapidly growing technological demand for lithium-ion batteries has prompted the development of novel cathode materials with high energy density, low cost, and improved safety. High voltage spinel, LiNi 0.5 Mn 1.5 O 4 (LNMO), is one of the most promising candidates yet to be commercialized. The two primary obstacles for this material are the inferior electronic conductivity and fast capacity degradation in full cells due to the high operating voltage. By systematically addressing these limitations, we succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 48 publications
1
55
0
Order By: Relevance
“…Therefore, it is necessary to evaluate whether the electrolyte used here is stable enough to undertake the high voltage of 4.65 V required by NMC811. As demonstrated in Note S1 (Supporting Information) and previous studies, [ 35,36 ] the used electrolyte in this study is stable up to 4.85 V. The images of the dissembled cells in Figure S4 (Supporting Information) show that there is still a noticeable amount of electrolyte left in the cells after cycling. Additionally, the reassembled cell with the cycled NMC811 and a new lithium‐metal anode (Figure S5, Supporting Information) still experiences a rapid increase in the cut‐off charge voltage.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, it is necessary to evaluate whether the electrolyte used here is stable enough to undertake the high voltage of 4.65 V required by NMC811. As demonstrated in Note S1 (Supporting Information) and previous studies, [ 35,36 ] the used electrolyte in this study is stable up to 4.85 V. The images of the dissembled cells in Figure S4 (Supporting Information) show that there is still a noticeable amount of electrolyte left in the cells after cycling. Additionally, the reassembled cell with the cycled NMC811 and a new lithium‐metal anode (Figure S5, Supporting Information) still experiences a rapid increase in the cut‐off charge voltage.…”
Section: Resultssupporting
confidence: 74%
“…As to the reasons for the aggravated electrode/electrolyte interactions and thicker CEI in NMC811, it is proposed to primarily result from the compositional difference between NMC811 and LNO. Specifically, although NMC811 requires a higher voltage to reach the given degree of delithiation, the electrochemical performance in Note S1 (Supporting Information), along with previous studies, [ 35,36 ] demonstrates that the used electrolyte is stable for this study. Meanwhile, recent studies have indicated that electrolyte oxidation decomposition on higher‐ and lower‐Ni NMC cathodes is not driven by cell voltage.…”
Section: Resultsmentioning
confidence: 60%
“…Because increasing research attention has been paid to thick electrode design, an overview of the research statistics in this field is essential to benchmark the current research status. Here, we summarize the information on the abovementioned electrode design parameters as well as energy/power density indicators from 62 publications related to thick electrodes, [ 8,9,12–15,20,21,24,39,40,43–45,50,62–104 ] (Table S2, Supporting Information) and the results of the statistical analysis are discussed in the following section.…”
Section: Literature Analysis Of Thick Electrodesmentioning
confidence: 99%
“…[19,20] Besides the modification on active materials, many cell components have also been optimized for high-voltage operation such as the binder and conductive agents. [21] However, the compatibility of the electrolyte with the charged state of LRLO is often neglected in the literature. The activation step ubiquitously seen in anionic redox materials occurs at 4.5 V versus Li + / Li 0 .…”
mentioning
confidence: 99%